2020
DOI: 10.2147/ppa.s274323
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Role of Medication Beliefs on Medication Adherence in Middle Eastern Refugees and Migrants Diagnosed with Hypertension in Australia</p>

Abstract: Purpose The study assessed the association between medication beliefs and adherence in Middle Eastern refugees and migrants in Australia, and also examined differences between the two groups regarding beliefs and adherence to medication. Patients and Methods A total of 319 Middle Eastern refugees and migrants with hypertension were approached via various social groups in Australia and asked to complete Arabic versions of the Beliefs about Medicine Questionnaire (BMQ) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…A recent comparative study in Australia showed that hypertensive Middle Eastern refugees, including Syrians, had more concerns about the side effects of hypertension treatment than migrants who had consciously left their country and were less exposed to the circumstances associated with displacement, which in turn led to significantly low adherence rates in the refugee group. 30 Considering that subjective perceptions and beliefs may determine a person’s health behaviours, 31 it is recommended that future studies assess the impact of this factor on adherence levels among syrians in Jordan by using multidimensional scales that account for the complexity of human perceptions and beliefs. Also, it is recommended to use mixed-methods research approaches involving quantitative and qualitative methods, as the former provides valuable information on persistence but is less precise in examining perceptual aspects.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparative study in Australia showed that hypertensive Middle Eastern refugees, including Syrians, had more concerns about the side effects of hypertension treatment than migrants who had consciously left their country and were less exposed to the circumstances associated with displacement, which in turn led to significantly low adherence rates in the refugee group. 30 Considering that subjective perceptions and beliefs may determine a person’s health behaviours, 31 it is recommended that future studies assess the impact of this factor on adherence levels among syrians in Jordan by using multidimensional scales that account for the complexity of human perceptions and beliefs. Also, it is recommended to use mixed-methods research approaches involving quantitative and qualitative methods, as the former provides valuable information on persistence but is less precise in examining perceptual aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of these studies suggest that the reasons behind the differences in medication adherence contribute to refugees' and migrants' differing perceptions of illness, culture and medications. 20 , 28 Research highlights the need for patient-centred interventions and processes to improve medication adherence. 22 Therefore, understanding these beliefs, and the differences between the two groups regarding their perceptions is crucial for developing interventions oriented towards better adherence to prescribed medications.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, developing a greater awareness of potential cultural barriers that may arise with patients from ethnic minority groups should be a priority 48–53 . Thus, healthcare professionals may be better equipped with strategies to overcome them to facilitate better and equal access to appropriate medicine review and supportive care 48,54–57 …”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50][51][52][53] Thus, healthcare professionals may be better equipped with strategies to overcome them to facilitate better and equal access to appropriate medicine review and supportive care. 48,[54][55][56][57] Communication is an important prerequisite for successful healthcare access and outcomes. 58 Due to the presence of a language barrier, studies have reported that ethnic minority patients with limited English demonstrate lower rates of medication adherence, make fewer visits to healthcare professionals, have reduced understanding of their conditions and treatment and develop increased medical complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation